Leadership divided : - Carucci, Ron A. (Jossey-Bass, 2006)
Leadership Divided tells the fictional suspense story of Brookreme Corporation, whose leaders are struggling to chart a course to the future. The story is a lesson in the kinds of relationships that can form between today's and tomorrow's leaders?relationships that can transform organizations. Using real cases and the voices of CEOs and senior executives, Leadership Divided provides compelling real-life examples of how such relationships enable organizations to outperform others.